Two new records of Meliolaceous black mildew fungi from India - Natekar, Pratik D.; Patil, Anjali P.; Patil, Chandrahas R.; Bhise, Mahendra R.; Kambhar, Sidanand V. (Phytotaxa, 2024)
Two black mildew fungi, Asteridiella leeicola and Meliola holarrhenicola were found on new host plants, Leea indica (Vitaceae) and Holarrhena pubescens (Apocynaceae), respectively. These species have not been reported from India. Therefore, the present report contributes new records for India. Taxonomic observations and microphotographs are provided for easy identification of taxa.